2018
DOI: 10.1186/s13012-018-0748-3
|View full text |Cite
|
Sign up to set email alerts
|

Supporting teams to optimize function and independence in Veterans: a multi-study program and mixed methods protocol

Abstract: BackgroundSuccessful implementation of new clinical programs depends on effectively establishing, reorganizing, or enhancing team structures and processes to coordinate the work of individuals who are interdependent in their tasks, manage relationships, and share responsibility for outcomes. However, a one-size-fits-all approach is rarely effective. In partnership with VA national clinical leaders and local clinical champions, the Optimizing Function and Independence VA Quality Enhancement Research Initiative … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
34
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 24 publications
(35 citation statements)
references
References 71 publications
0
34
0
Order By: Relevance
“…There are potentially some factors that support enhanced Veterans outcomes. There are some unique programs to optimize function and increase mobility for Veterans with disabilities that are provided by the VA SCI System of Care and associated programs to support community dwelling Veterans [35]. Veterans with SCI that enrolled in NSCID could have access to more services that focus on physical independence and mobility than Non-Veterans with SCI.…”
Section: Discussionmentioning
confidence: 99%
“…There are potentially some factors that support enhanced Veterans outcomes. There are some unique programs to optimize function and increase mobility for Veterans with disabilities that are provided by the VA SCI System of Care and associated programs to support community dwelling Veterans [35]. Veterans with SCI that enrolled in NSCID could have access to more services that focus on physical independence and mobility than Non-Veterans with SCI.…”
Section: Discussionmentioning
confidence: 99%
“…We describe a SW-CRT that is ongoing in 8 VHA hospitals as part of the Optimizing Function and Independence Quality Enhancement Research Initiative program (Function QUERI) [11]. STRIDE is an evidence-based supervised walking program for hospitalized older adults designed to reduce the negative consequences of immobility [12,13].…”
Section: Study Design Overviewmentioning
confidence: 99%
“…Initial positive results suggested that STRIDE had the potential to become a system-wide approach to address hospital-associated disability in the VHA; however, differences in resources, staffing, and priorities among other conditions in VHA facilities presented barriers to successful implementation at other sites. Therefore in 2016 we launched an ongoing project, Optimizing Function and Independence QUERI (known as "Function QUERI") to implement STRIDE in 8 additional VA hospitals [24]. One of the goals of Function QUERI is to study the process of starting a STRIDE program so that these lessons can be applied in broader efforts to promote hospital mobility programs.…”
Section: Stride Expansionmentioning
confidence: 99%
“…One of the goals of Function QUERI is to study the process of starting a STRIDE program so that these lessons can be applied in broader efforts to promote hospital mobility programs. Eight VA hospitals volunteered to begin STRIDE programs at their sites and were randomized to begin at a specific time [24]. To date, 4 of 8 have initiated their programs (hereafter referred to as expansion sites).…”
Section: Stride Expansionmentioning
confidence: 99%